A scalable and highly immunogenic virus‐like particle‐based vaccine against SARS‐CoV‐2. Issue 1 (20th September 2021) - Mohsen, Mona O.; Balke, Ina; Zinkhan, Simon; Zeltina, Villija; Liu, Xuelan; Chang, Xinyue; Krenger, Pascal S.; Plattner, Kevin; Gharailoo, Zahra; Vogt, Anne‐Cathrine S.; Augusto, Gilles; Zwicker, Marianne; et al.
Abstract: Background: SARS‐CoV‐2 caused one of the most devastating pandemics in the recent history of mankind. Due to various countermeasures, including lock‐downs, wearing masks, and increased hygiene, the virus has been controlled in some parts of the world. More recently, the availability of vaccines, based on RNA or adenoviruses, has greatly added to our ability to keep the virus at bay; again, however, in some parts of the world only. While available vaccines are effective, it would be desirable to also have more classical vaccines at hand for the future. Key feature of vaccines for long‐term control of SARS‐CoV‐2 would be inexpensive production at large scale, ability to make multiple booster injections, and long‐term stability at 4℃. Methods: Here, we describe such a vaccine candidate, consisting of the SARS‐CoV‐2 receptor‐binding motif (RBM) grafted genetically onto the surface of the immunologically optimized cucumber mosaic virus, called CuMVTT ‐RBM. Results: Using bacterial fermentation and continuous flow centrifugation for purification, the yield of the production process is estimated to be >2.5 million doses per 1000‐litre fermenter run. We demonstrate that the candidate vaccine is highly immunogenic in mice and rabbits and induces more high avidity antibodies compared to convalescent human sera. The induced antibodies are more cross‐reactive to mutant RBDs of variants of concern (VoC). Furthermore, antibody responses are neutralizing and long‐lived. In addition, the vaccine candidate was stable for at least 14 months at 4℃. Conclusion: Thus, the here presented VLP‐based vaccine may be a good candidate for use as conventional vaccine in the long term. Abstract : In this study, we describe a novel conventional COVID‐19 vaccine that consists of the RBM of SARS‐CoV‐2 genetically grafted onto the surface of our optimized cucumber‐mosaic virus‐like particles. We demonstrate that the vaccine candidate (mCuMVTT ‐RBM) is highly immunogenic in mice and rabbits, can efficiently neutralize SARS‐CoV‐2, and is stable and highly scalable. The induced antibodies show cross‐reactivity with VoC. Abbreviations: COVID‐19, coronavirus disease 2019; CuMVTT ‐VLPs, cucumber‐mosaic virus‐like particles; RBD, receptor‐binding domain; RBM, receptor‐binding motif; SARS‐CoV‐2, severe acute respiratory syndrome coronavirus 2; VOCs, variant of concerns.